Effects of different microbial agents on bedding treatment of ectopic fermentation of buffalo manure - Niu, Kaifeng; Chao, Chen; Zhang, Xinxin; An, Zhigao; Zhou, Jiayan; Yang, Liguo (Frontiers in Microbiology, 2022)
The rapid development of the farming industry has increased the amount of manure produced by livestock and poultry, causing increasingly prominent environmental pollution problems. In recent years, due to the increase in conventional bedding material costs, an increasing number of farmers choose to use harmless recycled manure as bedding. Manure bedding treatment of farms can not only solve the problem of manure pollution, but also resource utilization of manure and cost savings. This study compared the effects of five microbial agents ( Microbial agents A, B, C, E, F) on buffalo manure bedding treatment by testing the temperature, moisture content, pH, microbial bacteria distribution of buffalo manure ectopic fermentation, and screened the lowest cost and most effective agent. The changes of microbial bacteria distribution in different periods of bedding treatment were also detected. The results revealed that: agent A was eliminated because of poor fermentation effect and low fermentation temperature, which could not achieve the effect of harmless treatment. The other four agents of bacteria achieved a harmless effect, but the bedding treatment effect of agent F was significantly better than agent E, B, and C. In terms of the cost of agents: the cost of agent F required for fermenting 100m³ buffalo manure was the lowest, 1000yuan, followed by E (1200yuan), C (1750yuan), and B (1980yuan). In the process of ectopic fermentation bedding treatment of buffalo manure, Firmicutes, Bacteroidetes, Proteobacteria, Actinobacteria, and Chloroflexi were the major bacteria used. The process was divided into three periods; the heating period - high temperature period - cooling period, the high temperature period could reach more than 75℃, and a large number of pathogenic bacteria and harmful bacteria, and other miscellaneous bacteria in the pile were degraded, their species diversity was reduced, and the structure of bacterial flora had significant differences in different treatment periods. In conclusion, this study has provided a guide for the resource utilization of manure in cattle farms and the reduction of manure pollution to the environment.